2020
DOI: 10.1002/htj.21862
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of slip boundary conditions for the flow of nanofluid in the presence of an inclined magnetic field

Abstract: The inflated heat transport rate of nanofluids is of great interest to researchers. Conviction of nanosuspension with an enhanced model under the consideration of inclined magnetic field is also vital for the enhancement of heat transport rate. Therefore, in this article, an inclined magnetic field has been considered during a boundary layer flow over an extending sheet, with the sheet being permeable. The sequels of heat radiation, thermophoresis, and Brownian parameters are also taken into consideration in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…They observed that the skin friction decreases for higher stretching parameter values, whereas a reverse trend is observed in the case of Nusselt and microorganism numbers. Nayak et al 17 presented the effects of thermal radiation and MHD on nanofluid flows past an inclined surface. They found that an increase in thermal slip and inclination angle causes thinning of the thermal boundary layer, which results in the reduction of the liquid energy.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the skin friction decreases for higher stretching parameter values, whereas a reverse trend is observed in the case of Nusselt and microorganism numbers. Nayak et al 17 presented the effects of thermal radiation and MHD on nanofluid flows past an inclined surface. They found that an increase in thermal slip and inclination angle causes thinning of the thermal boundary layer, which results in the reduction of the liquid energy.…”
Section: Introductionmentioning
confidence: 99%
“…Anwar et al [2] analysed numerically the radiative MHD flow using the Laplace transformation. Researchers [13,14,21] looked into non-newtonian fluid several slip situations.…”
Section: Introductionmentioning
confidence: 99%